Effects of Low pH on Photosynthesis, Related Physiological Parameters, and Nutrient Profiles of Citrus - Long, An; Zhang, Jiang; Yang, Lin-Tong; Ye, Xin; Lai, Ning-Wei; Tan, Ling-Ling; Lin, Dan; Chen, Li-Song (Frontiers in Plant Science, 2017)
Seedlings of “Xuegan” (Citrus sinensis) and “Sour pummelo” (Citrus grandis) were irrigated daily with a nutrient solution at a pH of 2.5, 3, 4, 5, or 6 for 9 months. Thereafter, the following responses were investigated: seedling growth; root, stem, and leaf concentrations of nutrient elements; leaf gas exchange, pigment concentration, ribulose-1,5-bisphosphate carboxylase/oxygenase activity and chlorophyll a fluorescence; relative water content, total soluble protein level, H2O2 production and electrolyte leakage in roots and leaves. This was done (a) to determine how low pH affects photosynthesis, related physiological parameters, and mineral nutrient profiles; and (b) to understand the mechanisms by which low pH may cause a decrease in leaf CO2 assimilation. The pH 2.5 greatly inhibited seedling growth, and many physiological parameters were altered only at pH 2.5; pH 3 slightly inhibited seedling growth; pH 4 had almost no influence on seedling growth; and seedling growth and many physiological parameters reached their maximum at pH 5. No seedlings died at any given pH. These results demonstrate that citrus survival is insensitive to low pH. H+-toxicity may directly damage citrus roots, thus affecting the uptake of mineral nutrients and water. H+-toxicity and a decreased uptake of nutrients (i.e., nitrogen, phosphorus, potassium, calcium, and magnesium) and water were likely responsible for the low pH-induced inhibition of growth. Leaf CO2 assimilation was inhibited only at pH 2.5. The combinations of an impaired photosynthetic electron transport chain, increased production of reactive oxygen species, and decreased uptake of nutrients and water might account for the pH 2.5-induced decrease in CO2 assimilation. Mottled bleached leaves only occurred in the pH 2.5-treated C. grandis seedlings. Furthermore, the pH 2.5-induced alterations of leaf CO2 assimilation, water-use efficiency, chlorophylls, polyphasic chlorophyll a fluorescence (OJIP) transients and many fluorescence parameters, root and leaf total soluble proteins, H2O2 production, and electrolyte leakage were all slightly greater in C. grandis than in C. sinensis seedlings. Hence, C. sinensis was slightly more tolerant to low pH than C. grandis. In conclusion, our findings provide novel insight into the causes of low pH-induced inhibition of seedling growth and leaf CO2 assimilation.